Frequency of Vitamin D Deficiency in the Mothers of Low Birth-Weight Newborns: A Cross-Sectional Study - Komal Ashok, Abdul Hameed Radhan, Farzana Shaikh, Khuda Bux Khosa, Zamir Ahmed Qambrani, Suresh Kumar, Muhammad Nadeem Chohan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of vitamin D deficiency in the mothers of low birth-weight newborns Study design: A cross-sectional study Place and Duration: Postnatal/Neonatal ward, Liaquat University Hospital Hyderabad and Jamshoro, from December 2020 to June 2021 Methodology: The study includes full-term newborns who had low birth weights, regardless of gender, and who were admitted to a neonatal or postnatal unit. Each mother gave a 5ml blood sample, which was sent right away to the hospital laboratory. Within 24 to 48 hours following delivery, a diagnostic lab checked the mother’s vitamin D level. To determine the neonatal birth weight in kilograms, all the neonates were measured. All of the information about the maternal vitamin D level, the neonatal birth weight, and demographic data were entered after the reports had been collected. The researcher performed all measures. The proforma had all of the information. With SPSS version 20, data analysis was carried out. Results: The average age of the mother was 26.46 + 3.91 years. A total of 53.6% of newborns were males and 46.4% of newborns were female. Overall 90% of women were housewives, while 10% were employed. Women made up 68.6% of the reservations, while 31.45% were not. A total of 33.6% of all newborns underwent caesarean procedures, compared to a normal vaginal delivery rate of 66.4%. Eighty-seven percent of mothers were vitamin D deficient, and of them, 45.0% had mild deficiencies, 23.6% had moderate deficiencies, 12.1% had severe deficiencies, and 19.3% had normal vitamin D levels. Related to maternal age, newborn gender, and occupation, vitamin D deficiency was statistically insignificant (p>0.05), but it was statistically significant (p-0.05) according to a place of residence, educational attainment, SES, parity, booking status, and delivery method. Conclusion: Frequency of vitamin D deficiency was found to be highly prevalent among mothers, of neonates who presented with low birth weight. Keywords: Newborn, vitamin D, Birth weight